Expanding professional pharmacy services in European community setting: Is it cost-effective? A systematic review for health policy considerations. Issue 12 (December 2016) - Perraudin, Clémence; Bugnon, Olivier; Pelletier-Fleury, Nathalie
Highlights: Of the 21 studies identified, 13 have been conducted in United-Kingdom. Screening programs and smoking cessation services should be more widely available. Evidence for the efficiency of programs to improve treatment outcomes is not clear (e.g., medication review, educational and coaching program). Besides their efficiency, the integration of these services in the healthcare system depends on the national context. Abstract: Objective: To synthesize cost-effectiveness analyses on professional pharmacy services (PPS) performed in Europe in order to contribute to current debates on their funding and reimbursement. Methods: Systematic review in PubMed, Embase and the Centre for Reviews and Dissemination databases to identify full economic evaluation studies of PPS in community setting from 2004. Findings: Twenty-one studies were included, conducted in the United-Kingdom (n = 13), the Netherlands (n = 3), Spain (n = 2), Belgium (n = 1), France (n = 1) and Denmark (n = 1). PPS to enhance medicine safety (interprofessional meetings to reduce errors, n = 2) and access to medicines (minor ailment scheme, n = 1) were in favour of their cost-effectiveness in the UK context, but the evidence is not sufficient. Eleven studies assessed PPS to improve treatment outcomes of individual patients—such as pharmaceutical care services, medication review, educational and coaching program, disease support service, medicines management and telephone-based advisory for improving adherence. Findings were contradictory and did not lead to strong conclusion. Screening programs for different diseases showed robust positive results (n = 2) as well as smoking cessation services (n = 5) and should be considered to be more widely available in accordance with national context. Conclusions: The review provides arguments for the implementation of PPS aiming to improve public health through screening programs and smoking cessation services. However, further full economic evaluations are needed to support or refute the added value of other services.